The Northern Ireland Control Programmes for Infectious Cattle Diseases Not Regulated by the EU - Strain, Sam; Verner, Sharon; Campbell, Emma; Hodnik, Jaka Jakob; Santman-Berends, I. M. G. A. (Frontiers in Veterinary Science, 2021)
The disease control programmes for Bovine Viral Diarrhoea (BVD), Infectious Bovine Rhinotracheitis (IBR), Johne’s Disease (JD), Leptospirosis and Neosporosis are described including the approved diagnostic tools, diagnostic quality systems, and the role of vaccination (where appropriate). This paper describes the control programmes within NI, the challenges relating them, as well as assessing their impact and effectiveness. taking into consideration the quality of data available and number of herds participating. With the NI agricultural industry experiencing increasing financial pressures and post Brexit changes, the necessity of working to maximise the performance of bovine disease control programmes at the individual farm level as well as at the regional level is increasingly important. The programmes described fall into two categories with two distinct aims. Two managed by AHWNI, the BVD eradication and JD Dairy Control programmes seek to eradicate or control infection at the regional level. A further 5 programmes, covering BVD, JD, IBR, Leptospirosis and Neospora, are managed by the Agri-Food and Biosciences Institute (AFBI) and focus on facilitating eradication or control at the individual herd level. These latter programmes conform to the Cattle Health Certification Standards (UK) (CHeCS) which is a UK self-regulatory body set up to ensure consistency between different disease control schemes across herds. The largest of all the programmes described is the AHWNI BVD Eradication Programme which has led to significant reductions in infection incidence. Compliance with it has been high with more than 97% of all cattle alive at the end of 2020 having a BVD test status. The rolling annual incidence of BVD virus positive calves has fallen by 56% since the start of the compulsory programme in 2016. This decrease has occurred largely through industry initiatives to deal with BVD positives, including the voluntary culling of persistently infected (PI) animals by herd owners, a voluntary abattoir ban on the slaughter of BVD virus (BVDv) positive animals, and the inclusion of retention of a BVDv positive animal as a non-conformance in the industry-run Farm Quality Assurance Scheme. were implemented.